SOIL SHEAR STRENGTH PARAMETER ANALYSIS BASED ON BEHAVIOR ANALYSIS OF LANDSLIDE CASE - Dyah Wahyu Apriani; Umar Mustofa; Rachmad Hidayat (U Karst, 2020)
Slope failure is a complex event. It can provide useful information about the condition of soil parameters on the failed slope in the same way it can provide an opportunity to evaluate the stability of other slopes. To evaluate the occurence of slope failure, unit weight data and shear strength properties of soil are needed, as well as methods of analysis including failure mechanisms. One of the methods used to evaluate landslide events is reverse analysis. In this study, reverse analysis was carried out on landslides that occurred on the slopes of D-D 'and F-F' at the Integrated Campus Building of the Institut Teknologi Kalimantan. The finite element method is used to analyze the safety number of the slopes under review. From the results of the reverse analysis, it was obtained that the soil parameters at the time of collapse in the top layer resulted in the value of unit weight (γ) = 20 kN / m2, Cohesion (c) = 2 kPa and Internal friction angle (φ) = 27 ° . Slope failure occured due to an increase in soil volume weight value, as well as a decrease in soil shear strength parameters, namely cohesion and internal friction angle.